Efektivitas Model Pembelajaran Teams Games Tournament Berbantuan Media Tiktok dalam Meningkatkan Hasil Belajar Siswa - Navida Fatkhurrohmah Barasanti; Wikan Budi Utami; Yuniar Ika Putri Pranyata (Jurnal Inovasi Pendidikan Matematika (JIPM), 2025)
Low mathematics learning outcomes are often caused by a lack of student activity and monotonous learning. This research aims to determine the effectiveness of the Teams Games Tournament learning model assisted by TikTok media on student learning outcomes. This research uses a quasi-experimental method. The population in this study were all class VIII students at SMP Negeri 17 Malang, with a research sample using a cluster random sampling technique totaling 62 people. Data was obtained through a description test consisting of 5 questions whose validity and reliability were tested. In the analysis prerequisite tests use the normality test and homogeneity test. The hypothesis testing method used is the independent sample t test with a significance level of 0.05. The research results show that student learning outcomes after being given treatment are higher than before being given treatment using the Teams Games Tournament learning model assisted by TikTok media, because the significance results obtained are 0.00 < 0.05, so H0 is rejected. Thus, the Teams Games Tournament learning model assisted by TikTok media is effective in improving student learning outcomes at SMP Negeri 17 Malang.